2014
DOI: 10.1038/srep06319
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Discrimination between Proliferation and Neuronal and Astroglial Differentiation of Human Neural Stem Cells

Abstract: Neural stem cells (NSCs) are characterized by a capacity for self-renewal, differentiation into multiple neural lineages, all of which are considered to be promising components for neural regeneration. However, for cell-replacement therapies, it is essential to monitor the process of in vitro NSC differentiation and identify differentiated cell phenotypes. We report a real-time and label-free method that uses a capacitance sensor array to monitor the differentiation of human fetal brain-derived NSCs (hNSCs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…EIS has been utilized already to distinguish initially differentiated cells from their progenitors, but these studies concentrate only on one single impedance parameter (resistance or capacitance) and do not consider neuronal networks structures as well as a sufficient investigation period to qualitatively and quantitatively track the complete maturation process (Lee et al 2014;Park et al 2011). Another approach proved that neurons, astrocytes and their progenitors in suspension have different dielectric properties suitable for cell sorting (Flanagan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…EIS has been utilized already to distinguish initially differentiated cells from their progenitors, but these studies concentrate only on one single impedance parameter (resistance or capacitance) and do not consider neuronal networks structures as well as a sufficient investigation period to qualitatively and quantitatively track the complete maturation process (Lee et al 2014;Park et al 2011). Another approach proved that neurons, astrocytes and their progenitors in suspension have different dielectric properties suitable for cell sorting (Flanagan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that EFs induce neurite elongation of neural cells [ 2 , 38 40 ]. In the work by Hinkle et al ., Xenopus spinal neurons were cultured in the presence of EFs.…”
Section: Discussionmentioning
confidence: 99%
“…In the work by Li et al ., steady and pulsed DC EF stimulation directed the neurite extension of spiral ganglion neurons [ 2 ]. In the work by Lee et al ., some neurites extended after AC/DC stimulation on human NSCs cultured in differentiation medium [ 40 ]. In our study, the primary processes and the branches of mNPCs were clearly evident after stimulation by DC pulses for 48 h. Fig 3 demonstrates our finding that DC pulses promoted the elongated processes of mNPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Neural stem cells were shown to have differences in time-course capacitance when cultured on interdigitated capacitance sensors and cultured under different conditions [70]. Proliferation and differentiation into either neuronal or astroglial cells could be differentiated in real time.…”
Section: (Ii) Pluripotent Stem Cellsmentioning
confidence: 99%